Can mobile technology and new classroom environments help students to sit less, move more, and behave better? - Howie, Erin (Sports Medicine Australia, 2014)
Erin Howie, upcoming be active 2014 conference presenter, discusses how mobile learning technology is changing the physical environment of the primary school classroom.